On the number of partitions with a fixed largest part - Robbins, Neville (Utilitas Mathematica, 2000)
Let 1 ≤ k ≤ n. We derive formulas that enable the computation of Pk(n), Qk(n) which denote respectively the number of partitions of n, the number of partitions of n into distinct parts , such that k is the largest part.